Organised Abuse and Testimonial Legitimacy - Salter, Michael (2011)
This paper will discuss the relationship between sexual abuse, invalidation and testimonial legitimacy with a particular focus on organised abuse. Using qualitative data drawn from a study of adult survivors of organised abuse, the paper emphasises how strategies of invalidation, disbelief and minimisation are embedded in children’s experiences of organised abuse as well as in the response of others to organised abuse throughout their lifespan. This analysis troubles the distinction between everyday and legalistic notions of credibility and emphasises instead how the denial of testimonial legitimacy to children and women in a range of contexts is underpinned by relations of power that compound the gendered risks and harms of sexual abuse. The findings of this study suggest that the denial of testimonial legitimacy is a serious barrier to the wellbeing and safety of victims of sexual abuse, such as those disclosing organised abuse, whose life histories render them particularly vulnerable to strategies of invalidation.Sydney Institute of Criminology; School of Social Sciences at the University of Western Sydne